Envelope and phase statistics of Cauchy quadratures. Issue 13 (1st June 2016) - Li, Yawei; Li, Xiaofeng; Beaulieu, Norman C.; Fu, Zhizhong
Abstract : Non‐Gaussian quadratures, especially Cauchy quadratures, are widely used to model impulsive noise environments. The envelope and phase statistics of Cauchy quadratures are investigated. The probability density functions and cumulative distribution functions of the envelope and phase of Cauchy quadratures are given in closed‐form expression. The characteristics of the derived distributions are also discussed.